2008
DOI: 10.1108/02656710810854296
|View full text |Cite
|
Sign up to set email alerts
|

The value of quality improvements

Abstract: Purpose -To present a proactive quality costs measurement methodology, which describes the value of quality improvements and the implication of this value on customers' perception regarding the value of the product. Design/methodology/approach -By describing the perceived customer value in a dynamic term, it becomes possible to derive an analytical model that recognizes the implication of a company's efforts to improve design quality and conformance quality on product value as perceived by the customers. Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…The TQM approach, which is usually conducted in combination with FMEA and the fault tree analysis to resolve issues, has more prominent effects as compared to FMEA (Devadasan, Muthu, Samson, & Sankaran, 2003;Elmquist & Tehrani, 2008). Setijono and Dahlgaard (2008) suggested that from the standpoint of quality and cost, it can better assist enterprises in increasing the quality level, improving the overall profit, and reducing the risk of failures and eventually turns them into more valuable enterprises. Rodchua (2006) indicated that that it is difficult for enterprises to reduce the quality cost if they could not discover problems through the process of quality improvement.…”
Section: Failure Mode and Effects Analysismentioning
confidence: 99%
“…The TQM approach, which is usually conducted in combination with FMEA and the fault tree analysis to resolve issues, has more prominent effects as compared to FMEA (Devadasan, Muthu, Samson, & Sankaran, 2003;Elmquist & Tehrani, 2008). Setijono and Dahlgaard (2008) suggested that from the standpoint of quality and cost, it can better assist enterprises in increasing the quality level, improving the overall profit, and reducing the risk of failures and eventually turns them into more valuable enterprises. Rodchua (2006) indicated that that it is difficult for enterprises to reduce the quality cost if they could not discover problems through the process of quality improvement.…”
Section: Failure Mode and Effects Analysismentioning
confidence: 99%
“…In this stage the influence of quality costs to added value is also calculated. For that purpose, Setijono and Dahlgaard (2008) two-dimentional vector of influence is also calculated. First part of vector's equation .…”
mentioning
confidence: 99%
“…Part of tests, accomplished at the Technological Experiments Centre during the period 2008-04-01 -2011-01-01 is presented in Table. The data of only weakest parts of bicycle, where the risk of breaking is the highest according to test results are presented in this Table. Parts of bicycles, which didn't break during the tests detected that these parts are substantial, reliable and quality is quite enough. Total quality of the assembled bicycle depends on reliability and quality of all parts of bicycle [9]. As shown in the Table, the weakest parts of tested bicycles are brakes, carriers and front fork.…”
Section: Testing Resultsmentioning
confidence: 99%